Anisotrpic friction behavior of charcoal and the influence of humidity. (April 2015) - Kumar, N.; Radhika, R.; Chakravarty, S.; Pandian, R.; Ravindran, T.R.; Dash, S.; Tyagi, A.K.
Abstract: Tribo-tests were carried out on pyrolyted wood derived charcoal specimen in the directions of "flat-face" and "curved-face". In former direction, an ultra-low friction coefficient 0.03 was measured in a high humid condition with 75% relative humidity. Eventually, the friction coefficient becomes 0.45 when the humidity level decreased to 10%. However, under similar tribo-test condition, the friction coefficient is high 0.1 in the "curved-face" of charcoal specimen at 75% humidity. This value further increased to 0.8 at humidity level of 10%. Large amount of polar functional groups, oxygen complexes and water molecules was observed on the "flat-face" due to the presence of microscopic pores which act as a reservoir to lubricate the sliding surfaces. Graphical abstract: Highlights: Direction dependent tribology test on the coal specimen is characterized. Microstructure and chemical behavior of coals and tribology behavior is characterized. Characterization of humidity dependent friction behavior in coal specimen.